Precipitation impacts on earthen architecture for better implementation of cultural resource management in the US Southwest - Sharlot Hart (SpringerOpen, 2021)
Abstract Changing seasonal precipitation patterns prompted by climate change are likely causing increasing degradation of adobe architecture in the American Southwest. This deterioration includes surface erosion and catastrophic collapse. This study examines the impact of changing rainfall patterns on untreated adobe walls to understand how damage occurs and anticipate future impacts. To complete the study, we constructed 20 adobe test walls. Using a portable rain simulator, each wall was subjected to two rainfall experiments: high-intensity rainfall simulations (rain intensity variable) and low-intensity rainfall simulations (rain event number variable). Wall-degradation metrics (material loss, volume loss, affected surface area, and cavity depth) were calculated for each wall using pre- and post-simulation LiDAR scans. Internal wall moisture was also measured with embedded volumetric water content sensors. In the high-intensity experiment, the lines of best-fit for material loss and affected surface area show that surface erosion increases with rain intensity, while cavity depth remains consistent. Linear models and post-hoc tests indicate material loss and affected surface area is significantly different for each high-intensity rainfall treatment. Furthermore, the interior of each wall remained relatively dry demonstrating that rain intensity is not a strong predictor of interior wall moisture. In the low-intensity rainfall experiment, the rainfall simulations yielded statistically similar erosion and interior wall moisture results. Greater infiltration occurred under low-intensity long-duration rain conditions, while greater surficial damage occurred under high-intensity rain conditions. In conclusion, changing weather regimes are bringing more intense rainfall events to the arid American Southwest. This study suggests that more frequent high intensity rain events will cause increasing damage to adobe walls. Resource managers will need to adapt current management strategies to account for this change.